Calculating the Electrochemically Active Surface Area of Iridium Oxide in Operating Proton Exchange Membrane Electrolyzers. Issue 12 (1st January 2015) - Zhao, Shuai; Yu, Haoran; Maric, Radenka; Danilovic, Nemanja; Capuano, Christopher B.; Ayers, Katherine E.; Mustain, William E.
Abstract : Iridium oxide is one of the most common anode catalysts in commercial proton exchange membrane (PEM) electrolyzers because of its strong mix of high activity and stability under oxygen evolution reaction (OER) conditions. Unfortunately, benchmarking iridium oxide OER catalysts has proven difficult since IrO2 cannot undergo proton underpotential deposition like platinum and other transition metal eletrocatalysts, making it difficult to estimate the electrochemically active surface area (ECSA), as well as OER specific and mass activity. In this work, we propose a method to calculate the ECSA of iridium oxide in an operating PEM electrolyzer. A universal constant, 596 (± 21) μC/cm 2, was obtained from the correlation of pseudocapacitive charge and ECSA of iridium oxide. In the membrane electrode assembly (MEA), the calculated ECSA (1.81 (±0.065) m 2 over a 25-cm 2 geometric area) showed an iridium oxide catalyst utilization of ∼93%. Additionally, the IrO2 OER specific and mass activities at 80°C, 1.6 V in an operating PEM electrolyzer were 0.401 (±0.014) mA/cm 2 and 132 mA/mg, respectively.